Raport Berbasis Web dengan Studi Kasus Kelas 4A pada SD YPPK Santo Petrus Nabire - Ester Ayuk Pusvita; Wahyu Adi Saputra Sinaga (STMIK Pesat Nabire, 2024)
This study aims to develop and implement a web-based reporting system with a case study on Class 4A at SD YPPK Santo Petrus Nabire. The system is designed to improve efficiency in the creation and management of academic reports and to facilitate access for teachers, students, and parents. In this research, the system development method uses a waterfall approach that includes requirement analysis, system design, implementation, and testing. The results of this study indicate that the web-based reporting system can provide ease in the academic reporting process and enhance parental involvement in monitoring students' academic progress.